Congenital hypogonadotropic hypogonadism and constitutional delay of growth and puberty have distinct genetic architectures. Issue 4 (April 2018) - Cassatella, Daniele; Howard, Sasha R; Acierno, James S; Xu, Cheng; Papadakis, Georgios E; Santoni, Federico A; Dwyer, Andrew A; Santini, Sara; Sykiotis, Gerasimos P; Chambion, Caroline; Meylan, Jenny; Marino, Laura; et al.
Abstract : Objective: Congenital hypogonadotropic hypogonadism (CHH) and constitutional delay of growth and puberty (CDGP) represent rare and common forms of GnRH deficiency, respectively. Both CDGP and CHH present with delayed puberty, and the distinction between these two entities during early adolescence is challenging. More than 30 genes have been implicated in CHH, while the genetic basis of CDGP is poorly understood. Design: We characterized and compared the genetic architectures of CHH and CDGP, to test the hypothesis of a shared genetic basis between these disorders. Methods: Exome sequencing data were used to identify rare variants in known genes in CHH ( n = 116), CDGP ( n = 72) and control cohorts ( n = 36 874 ExAC and n = 405 CoLaus). Results: Mutations in at least one CHH gene were found in 51% of CHH probands, which is significantly higher than in CDGP (7%, P = 7.6 × 10 −11 ) or controls (18%, P = 5.5 × 10 −12 ). Similarly, oligogenicity (defined as mutations in more than one gene) was common in CHH patients (15%) relative to CDGP (1.4%, P = 0.002) and controls (2%, P = 6.4 × 10 −7 ). Conclusions: Our data suggest that CDGP and CHH have distinct genetic profiles, and this finding may facilitate the differential diagnosis in patients presenting with delayed puberty.